Mustache baby - Heos, Bridget; Ang, Joy (New York : Clarion Books, 2013)
"A picture book about baby Billy, who is born with a mustache, and his parents, who must figure our if it's a Good-Guy mustache, or a Bad-Guy mustache"--Provided by publisher.
Keywords: Babies -- Fiction; Behavior -- Fiction; Mustaches -- Fiction; Humorous stories; Infants -- Juvenile fiction; Conduct of life -- Juvenile fiction; Mustaches -- Juvenile fiction; Conduct of life; Infants; Mustaches; Fiction; Juvenile works